Pathogenesis, risk factors and therapeutic options for autoimmune haemolytic anaemia in the post‐transplant setting. (30th June 2021) - Gabelli, Maria; Ademokun, Christine; Cooper, Nichola; Amrolia, Persis I.
Summary: Autoimmune haemolytic anaemia (AIHA) is a rare complication of allogeneic haematopoietic stem cell transplantation (HSCT), observed with an incidence of 1–5%. Paediatric age, diagnosis of non‐malignant disease, lympho‐depleting agents in the conditioning regimen, use of unrelated donor, graft versus host disease and infections have been associated with a higher risk of AIHA post HSCT. Post‐HSCT AIHA is associated with high mortality and morbidity, and it is often very difficult to treat. Steroids and rituximab are used with a response rate around 30–50%. These and other therapeutic strategies are mainly derived from data on primary AIHA, although response rates in post‐HSCT AIHA have been generally lower. Here we review the currently available data on risk factors and therapeutic options. There is a need for prospective studies in post‐HSCT AIHA to guide clinicians in managing these complex patients.